2021
DOI: 10.1007/s11469-021-00559-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Brief Group Intervention Program for Young Adults with Gaming-Related Problems

Abstract: Excessive digital gaming can have unfavorable effects on gamers’ well-being and everyday functioning. The aims of this study were to investigate the effects of a novel group intervention “Limitless Gaming Bootcamp” on (i) gaming disorder (GD) tendencies, (ii) the amount of time spent on leisure activities, and (iii) subjective well-being among Finnish young adults, and to determine the persistence of the intervention’s influence over time. A one-group pre- and post-test design with no control group was used. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Recently, a randomized controlled trial evaluating the efficacy of a manualized CBT program for gaming disorder found that most patients (69%) who received the intervention showed remission compared with less than one-fourth (24%) of those in a waitlist control group 154 . Other approaches that have been tested in clinical trials include motivational interviewing and counseling, family therapy, and psychosocial rehabilitation 204,216 .…”
Section: Implications Of the Gaming Disorder Diagnosismentioning
confidence: 99%
“…Recently, a randomized controlled trial evaluating the efficacy of a manualized CBT program for gaming disorder found that most patients (69%) who received the intervention showed remission compared with less than one-fourth (24%) of those in a waitlist control group 154 . Other approaches that have been tested in clinical trials include motivational interviewing and counseling, family therapy, and psychosocial rehabilitation 204,216 .…”
Section: Implications Of the Gaming Disorder Diagnosismentioning
confidence: 99%
“…In addition to the “typical” individual interventions, it should be considered to address environmental risk factors (e.g., the peer group; Lee, Kim, & Lee, 2019 ). Group elements might also be well accepted and were found to be particularly effective in a non-randomized pilot study aimed to reduce the severity of IGD in young individuals aged 18–29 years ( Männikkö, Mustonen, Tanner, Vähänikkilä, & Kääriäinen, 2021 ). Nevertheless, further robust and methodically good studies evaluating the efficacy of such interventions in the context of IUD are needed ( Grist et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…9.52% of the studies provided short-term follow-up evaluations: 1 study at 28 days (King et al, 2017) and another at 4 weeks . Five studies (23.81%) carried out mid-term evaluations, specifically at 3 (Sakuma et al, 2017;Torres-Rodríguez et al, 2018) and at 6 months (Deng et al, 2017;Männikkö et al, 2021;Pornnoppadol et al, 2018). Two studies (9.52%) carried out long-term evaluations at 12 months (Nielsen et al, 2021;Százs-Janocha et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, some studies found significant differences in some of the variables, but not in others, for example: Sakuma et al (2017) found reductions in daily and weekly game time, but not in the days per week. Another study (Pallesen et al, 2015) found decreases in the severity of symptoms reported by parents, but not in those reported by the participants themselves; and 4 studies (King et al, 2017;Männikkö et al, 2021;Nielsen et al, 2021;Százs-Janocha et al, 2020) did not show decreases in playing time, although they did so in the severity of the symptom. Finally, the study by Li and Wang (2013) was the only one that did not find statistically significant differences in the outcome variable studied: severity of symptoms.…”
Section: Effects Of Interventionsmentioning
confidence: 97%